The designing and patenting of an improvement in hay tools - McCall, W. T. (My University, 1908)
Introduction: Few of the younger generation of today realize that practically every tool that is in present use on the farm is the product of the investitive genius of the past century. It is difficult for the average person to believe that the Machinery Age in which we are now living had its inception in times so recent as to be easily remembered by our grandparents or even by our parents.
Citation: McCall, W. T. The designing and patenting of an improvement in hay tools. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Tools; Agriculture; Hay; Patents; Graduating theses; Senior theses; Theses